Long-Term Retrospective Follow-Up of Fresh Osteochondral Allograft Transplantation for Steroid-Associated Osteonecrosis of the Femoral Condyles. (January 2021) - Early, Samuel; Tírico, Luís E. P.; Pulido, Pamela A.; McCauley, Julie C.; Bugbee, William D.
Objective: No studies currently exist with long-term follow-up of use of osteochondral allografting (OCA) for treatment of steroid-associated osteonecrosis of femoral condyles in young, active patients who wish to avoid total knee arthroplasty (TKA). We evaluate the extent to which fresh osteochondral allografts can (1) prevent or postpone need for prosthetic arthroplasty and (2) maintain long-term clinically meaningful decrease in pain and improvement in function at mean 11-year follow-up. Design: Twenty-five patients (33 knees) who underwent OCA transplantation for osteonecrosis of the knee between 1984 and 2013 were evaluated, including 22 females and 11 males with average age of 25 years (range, 16-48 years). Mean total allograft surface area was 10.6 cm 2 (range, 4.0-19.0 cm 2 ). Evaluation included International Knee Documentation Committee (IKDC) scores, Knee Society function (KS-F) score, and modified (for the knee) Merle d'Aubigné-Postel (18-point) score. Results: OCA survivorship was 90% at 5 years and 82% at 10 years. Twenty-eight of 33 knees (85%) avoided arthroplasty and 25 of 33 knees (73%) avoided other surgical intervention. Mean IKDC pain score improved ( P = 0.001) from 7.2 preoperatively to 2.8 at latest follow-up, mean IKDC function score increased ( P = 0.005) from 3.3 to 6.5, and mean IKDC total score improved ( P = 0.001) from 31.9 to 61.1. Mean KS-F score improved ( P = 0.003) from 61.7 to 87.5. Mean modified Merle d'Aubigné-Postel (18-point) score improved ( P < 0.001) from 11.4 to 15.1. Conclusions: Our findings suggest that OCA transplantation is a reasonable surgical treatment option for steroid-associated osteonecrosis of the femoral condyles, with durable long-term outcomes.